2021
DOI: 10.1186/s12882-021-02262-9
|View full text |Cite
|
Sign up to set email alerts
|

An intersectional gender analysis in kidney transplantation: women who donate a kidney

Abstract: Background Living-donor transplantation is the best treatment option in patients with chronic kidney failure. Global data show that women are less likely to be kidney recipients than men but are more likely to become living kidney donors. We explored the experience of women who donate a kidney to relatives with biological and socio-cultural ties and to understand the similarities and differences in their experience. Methods A qualitative hermeneuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Women presented overall more frequently as potential donors, independent of the evaluation outcome, which is analogous to previous published data (22,28). Altruism and a more paternalistic approach of women toward their relatives have been associated with this finding (29). The higher proportion of men in need of a kidney transplant has been documented in other studies as well (12,23), which has been associated to a higher risk of progression of chronic kidney disease (CKD) and ESKD among men (30).…”
Section: Discussionsupporting
confidence: 82%
“…Women presented overall more frequently as potential donors, independent of the evaluation outcome, which is analogous to previous published data (22,28). Altruism and a more paternalistic approach of women toward their relatives have been associated with this finding (29). The higher proportion of men in need of a kidney transplant has been documented in other studies as well (12,23), which has been associated to a higher risk of progression of chronic kidney disease (CKD) and ESKD among men (30).…”
Section: Discussionsupporting
confidence: 82%
“…A study conducted by us also showed multiple factors that were associated with the refusal of the recommended regime of dialysis (GULZAR et al, 2022). So whatever the reason for refusal it impacts the healthcare system of the country and makes it difficult to deal with the increased number of emergencies (Rota-Musoll et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Musol et al evaluated the role of gender in living kidney donation and reported that women related to recipients considered kidney donation as a natural process and donated organs with an optimistic attitude and disregard for their own health. The same study emphasized that wives considered kidney donation as a way to avoid assuming the role of caregiver for their husbands and to protect their children (21).…”
Section: Discussionmentioning
confidence: 99%